Politicas de formação de professores para o ensino de ciências da natureza:uma análise dos documentos oficias - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This dissertation addresses public policies aimed at teacher education for the teaching of Natural Sciences in Brazil. The study seeks to understand how educational policies expressed in official documents guide initial teacher education, based on the following research question: How do public policies expressed in official documents guide the initial education of teachers for the teaching of Natural Sciences? The general objective is to analyze the educational guidelines and policies present in official documents that guide the initial education of teachers for the teaching of Natural Sciences. The specific objectives are: (1) to identify and describe the main official documents that regulate this education; (2) to analyze how these documents address the competencies and knowledge required for teaching; and (3) to discuss the implications of public policies on teacher education for pedagogical practice in this field.This research is part of Line 2 – Educational Policies, Curriculum Production and Social Demands, of the Graduate Program in Teaching at the Federal University of Pampa, which encompasses studies focused on the analysis of educational policies, curriculum production, and social demands, in alignment with contemporary or past global and local agendas. In this sense, the study engages with this research line by investigating normative documents that structure and guide initial teacher education, considering their implications for curriculum organization, pedagogical practice, and the education and professional work of teachers in the field of Natural Sciences in Basic Education. A qualitative approach was adopted, based on documentary analysis and a systematic literature review. Official documents were analyzed, such as the National Common Base for Initial Teacher Education for Basic Education (BNC- Formação), the National Curriculum Guidelines (DCNs), the National Curriculum Parameters for Secondary Education (PCNEM), and the National Curriculum Guidelines for Secondary Education (OCNEM). Data analysis was carried out using Content Analysis methodology, as proposed by Bardin (2011), which enabled the identification of three main categories: (i) regulations and guidelines for initial teacher education; (ii) teaching knowledge and competencies for pedagogical practice; and (iii) challenges and tensions in teacher education and practice.The results indicate normative and conceptual advances in teacher education policies, especially regarding the recognition of interdisciplinarity, the articulation between theory and practice, and the need for critical and reflective education. However, challenges remain concerning the implementation of these guidelines, regional inequalities, and the integration between university and school. It is concluded that it is essential to strengthen public policies sensitive to territorial specificities and social demands, ensuring the professional recognition of teachers and promoting a critical, contextualized, and socially committed initial education capable of contributing to transformative science education.
Teacher training policies for the teaching of natural sciences: an analysis of official documents
Keywords: Formação docente; Políticas públicas; Ciências da natureza; Documentos oficiais; Interdisciplinaridade; Teacher education; Public policies; Natural sciences; Official documents; Interdisciplinarity; CIENCIAS HUMANAS